COMPARISON OF EJECTION FRACTION AND END VOLUMES OF THE LEFT VENTRICLE AS INDICATORS OF THE SEVERITY OF HEART FAILURE - Dinara Sh. Gazizova (Кубанский научный медицинский вестник, 2019)
Aim. To demonstrate that the end volumes are indicative of the severity of the left ventricle pathological condition not only under preserved, but also under reduced ejection fraction. Material and methods. 32 patients with dilated cardiomyopathy and severe heart failure, as well as with complete monitor and computer and echocardiographic control were examined. Results. The sensitivity of the ejection fraction and end volumes to the severity of heart failure (stroke index from 15.3 to 57.2, average 29.5±1.6; ejection fraction from 16.5 to 48.0, average 27.4±127; heart rate from 52 tо 113, average 81.8±2.4) was established. It is shown that the percentage change (sensitivity) of the ejection fraction (55%) is much lower than that of the end diastolic volume index (190%) and that of the end systolic volume index (438%) to the severity of heart failure. Conclusion. Indices of end-diastolic and end-systolic volumes of critical patients with dilated cardiomyopathy are more sensitive to the severity of heart failure than the ejection fraction. It is advisable to use end volumes as indicators of heart failure. An adequate quantitative assessment of the severity of heart failure should include the heart rate (duration of the cardiac cycle T).